Typhoid Fever due to Extended Spectrum β-Lactamase-Producing Salmonella enterica Serovar Typhi: A Case Report and Literature Review - Abdul Azeez Ahamed Riyaaz; Vindya Perera; Sabaratnam Sivakumaran; Nelun de Silva (Case Reports in Infectious Diseases)
Emergence of cephalosporin-resistant strains of Salmonella enterica serovar Typhi is a cause of concern in the management of enteric fever. Cephalosporin resistance in Salmonella species is mainly due to the production of extended-spectrum β-lactamases (ESBLs). The majority of ESBLs in Salmonella enterica serovar Typhi are derivatives of the TEM, SHV, and CTX-M β-lactamase families. Of these, CTX-M appears to be predominant. This paper discusses the detection and molecular characterization of an ESBL-producing Salmonella enterica serovar Typhi strain isolated from a patient who was admitted to a private hospital in Sri Lanka. The three main types of β-lactamases such as TEM, SHV, and CTX-M were identified in this isolate. This case report from Sri Lanka contributes to the knowledge of the increasingly reported cases of typhoid fever due to Salmonella enterica serovar Typhi resistant to β-lactamase by ESBL production.